Dermal Pharmacokinetics of Terpinen-4-ol Following Topical Administration of Zingiber cassumunar (plai) Oil - Chooluck, Kotchaphan; Singh, Rajendra P.; Sathirakul, Korbtham; Derendorf, Hartmut (Planta Medica, 2012)
The purpose of this study was to investigate dermal pharmacokinetics of terpinen-4-ol in rats following topical administration of plai oil derived from the rhizomes of Zingiber cassumunar Roxb. Unbound terpinen-4-ol concentrations in dermal tissue were measured by microdialysis. The dermal pharmacokinetic study of terpinen-4-ol was performed under non-occlusive conditions. The oil was topically applied at a dose of 2, 4, and 8 mg/cm2 plai oil corresponding to the amount of 1.0, 1.9, and 3.8 mg/cm2 terpinen-4-ol, respectively. Following topical application of the oil, terpinen-4-ol rapidly distributed into the dermis and demonstrated linear pharmacokinetics with no changes in the dose-normalized area under the concentration-time curves across the investigated dosage range. The mean percentages of free terpinen-4-ol distributed in the dermis per amount of administered were 0.39 ± 0.06 %, 0.41 ± 0.08 %, and 0.30 ± 0.03 % for 2, 4, and 8 mg/cm2 doses, respectively. The dermal pharmacokinetics of terpinen-4-ol could provide information for its further formulation development and therapy schedules.
Keywords: terpinen-4-ol; Zingiber cassumunar; Zingiberaceae; plai oil; dermal pharmacokinetics; microdialysis